POLINOMIAL CHEBYSHEV PADA SYARAT BATAS SERAP GELOMBANG AKUSTIK DUA DIMENSI - Mohammad Mahfuzh Shiddiq (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2016)
The problem of boundary conditions in wave equations has many types and methods of completion. One of the problem of boundary conditions is the absorbing boundary condition of the wave equation. This absorbing boundary requirement arises as a result of natural domains on unlimited wave propagation problems and requires large calculations. A numerical solution is inevitable in this type of wave equation. The numerical solution that will be discussed in this paper is to approach the solution of the problem of two-dimensional acoustic wave propagation by using chebyshev polynomial. Several comparison of solution results by using other approaches that have been done are also given to show the effectiveness of which solutions are better.